Cooperation and Mutual Relationships of Cities and their Hinterlands with Regard to the Operation of EU Integrated Development Instruments - Binek, Jan; Opravil, Zdeněk; Chmelař, Roman; Svobodova, Hana (Quaestiones Geographicae, 2016)
This paper deals with the institutional and factual readiness of cities and villages in the Czech Republic to use Integrated Territorial Investments (ITI). On the basis of a questionnaire survey carried out in May 2014 among representatives of 69 municipalities around the core cities of Brno, Jihlava, Olomouc and Hradec Králové - Pardubice as well as a comparison of several model agglomerations, it identifies the main problems and proposes solutions to them. The main theme of this paper is to evaluate the formation of partnerships of municipalities and the process of creating integrated strategies for metropolitan areas. The paper also deals with the relationships and functional links between cities and villages and their hinterland, the common development issues and the existing structures of cooperation and communication. In the conclusion possible recommendations are given to improve the ITI functioning in the Czech Republic on the basis of both, the assessment of the situation in the Republic itself and the reflection on developments in other EU countries.